Aplikasi Pemetaan Objek Pariwisata Kabupaten Bandung Berbasis Geographic Information System - Wibowo, Eddy Setiawan; Prasetyo, Putri Lutfiana Weebee; Uzzukru, Reival Muhamad Asyari; Fauzia, Miladyna; Permana, Sidik (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Bandung Regency has great tourism potential, but providing integrated and easily accessible tourism information remains a major challenge. This study aims to develop a Geographic Information System (GIS)-based application that can provide interactive and structured tourist location information. The application is designed to improve information accessibility, assist tourists in determining destinations, and support tourism promotion in Bandung Regency. The research method used is Research and Development (R&D) with an Agile Development approach. The development process includes problem identification, geographic and descriptive data collection, user needs analysis, system design, application development using GIS technology, and testing through alpha and beta tests. Implementation uses technologies such as Leaflet, JavaScript, PHP, MySQL, and Bootstrap. The results show that this GIS application successfully provides easy access to tourism information through features like an interactive map, location search, tourism category filters, and comprehensive data presentation. Additionally, the application offers a responsive interface compatible with various devices, making it easily accessible via smartphones and computers. The use of this application is expected to enhance the tourist experience, expand tourism promotion, and assist local governments in digitally managing tourism data. With the presence of this application, issues related to the accessibility of tourism information in Bandung Regency can be effectively resolved, while also encouraging sustainable growth in the regional tourism sector